Performance Management of State Civil Apparatus in Indonesia - Pratomo, Hanindyo Suryo; Nugraheni, Jacika Pifi (Manunggal Halim Jaya, 2026)
New public management represents an innovative paradigm in public administration, emphasizing results achievement, information transparency, and accountability for services to citizens. Performance management serves as the core element to realize this results orientation by measuring inputs, processes, outputs, and outcomes of government activities. This study aims to introduce ASN performance management in Indonesia as a manifestation of new public management using a qualitative approach. Findings reveal that rigid bureaucracy and low public service quality continue to impede administrative progress in Indonesia, positioning ASN performance management based on achievements as a strategic solution to enhance employee productivity and overall public service quality.